Regulatory Defect of Glycolysis in Human Lipoma. Issue 5898 (19th January 1974) - Atkinson, J. N. C.; Galton, D. J.; Gilbert, C.
Abstract : A metabolic defect has been observed in extracts of lipomata in which citrate fails to inhibit the conversion of glucose-6-phosphate to glyceride-glycerol. Phospho-fructokinase extracted from lipomata was less sensitive to inhibition by citrate than the enzyme of normal adipose tissue. However, maximal rates of lipogenesis (from glucose or palmitate) and lipolysis (stimulated with isoprenaline) in lipomata were similar to those of normal adipose tissue. This work suggests that loss of negative feedback control of regulatory enzymes may be an early feature in the development of neoplasia.